Association between pre-operative right ventricular impairment on transthoracic echocardiography and outcomes after conventional and minimally invasive mitral valve surgery. Issue 8 (10th November 2021) - Abdelrahman, Amr; Dębski, Maciej; Qadri, Syed; Guella, Elhosseyn; Tay, Justin; Wong, Kenneth Y. K.; Zacharias, Joseph
Abstract: Background: Right ventricular (RV) impairment may have prognostic value in patients undergoing mitral valve surgery. It is unclear whether RV dysfunction predicts long-term mortality, especially in the era of minimally invasive mitral surgery. Methods: We performed a retrospective analysis of consecutive patients referred for conventional ( via sternotomy) and minimally invasive mitral valve surgery (MIMVS) between 01 January 2013 and 29 August 2018 in a tertiary cardiac centre. We truncated follow-up times at 25 March 2020. RV impairment was defined by reduced RV longitudinal function (TAPSE <17 mm) and/or dilated basal RV diameter (RVD1 > 42 mm). Primary outcome was all-cause mortality. Results: The study cohort included 359 patients followed up for a median period of 4.2 (1.8) years. MIMVS approach was performed in 127 (35.4%) and conventional approach in 232 (64.6%) patients of whom 36 (28%) and 45 (19%), respectively, had RV impairment. EuroSCORE II was significantly higher in patients with RV impairment compared with patients with preserved RV function, irrespective of the surgical approach. Consequently, in both groups, patients with RV impairment had significantly higher mortality compared to patients with preserved RV function. RV impairment adjusted for EuroSCORE II predicted mortality in the whole cohort (HR 2.139, 95% CI 1.249–3.663) and in conventional approach (HR 2.361, 95% CI 1.249–4.465) in contrast to MIMVS (HR 1.570, 95% CI 0.493–4.997). Conclusion: In this real world cohort, patients with RV impairment and/or dilation had reduced long-term survival following both conventional surgery and MIMVS. Patients should be referred to surgery prior to worsening of RV function.